Ciência de dados e ciência da informação: guia para alfabetização de dados para bibliotecários - Reis, Makson de Jesus (2019)
A literature dissertation containing developmental skills and skills in literacy and data management for librarians. Thus, an evolutionary process in the paradigms of Thomas Kuhn, a process of discussion and understanding about the paradigm that is based on data, is presented in its theoretical reference. Scientific research is transformed by the vast amount of information by research and other means emerging or called data. The career to the science in the science of the date, the science of the date and the science of the date and the resource of the date and the progressions and the science. It also discusses the interdisciplinarity between data from Science and Science, for the emergence of data librarianship, as the field of action for the so-called data librarian. In this sense, the skills and competences necessary for their formation are presented, based on the competency matrix of Chantel Ridsdale (2015). Used as a research student, at the State University of Feira de Santana (UEFS), as research professor for the data literacy course for librarians of the institution. It is presented as a product of the dissertation, a guide that serves as a theoretical basis for the practice of data literacy and data management. It is concluded that the product presents innovative features and contributes with a series of data in Information Science. BICEN / UFS librarian in training and library services.